2017
DOI: 10.3390/su9040601
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Sustainability Logic on Carbon Disclosure in the Global Logistics Industry: The Case of DHL, FDX and UPS

Abstract: As a significant contributor to carbon emissions, global logistics companies are under scrutiny from various stakeholders, and respond by disclosing carbon-related information in the form of carbon reports. Carbon disclosure is, however, a mainly voluntary practice that allows for a broad range of interpretation from the management field, which leads to different approaches to the measurement and reporting of carbon-related information. From a theoretical perspective, these different carbon-disclosure approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 49 publications
1
33
0
2
Order By: Relevance
“…For example, the mission statements on climate change of the multinational company DHL indicate a shift of the sustainability logic to a closer position to the company's functioning in recent years (Herold & Lee, ). In 2011, the statements DHL issued regarding climate change stated that “carbon efficiency is (…) directly related to (…) cost efficiency” (CDP, , p. 3), indicating a focus on the market logic (Schaltegger & Burritt, ).…”
Section: Institutional Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the mission statements on climate change of the multinational company DHL indicate a shift of the sustainability logic to a closer position to the company's functioning in recent years (Herold & Lee, ). In 2011, the statements DHL issued regarding climate change stated that “carbon efficiency is (…) directly related to (…) cost efficiency” (CDP, , p. 3), indicating a focus on the market logic (Schaltegger & Burritt, ).…”
Section: Institutional Pressuresmentioning
confidence: 99%
“…In fact, the presence of carbon disclosure can be attributed to the adoption of the sustainability logic (Herold & Lee, ; Herold, ; Schaltegger & Hörisch, ). The sustainability logic reflects the integration of “sustainability” and “climate change” principles into a company's value system due to a potential legitimacy gap, which can be defined as “where corporate performance remains unchanged, but societal expectations about that performance have changed” (Hrasky, , p. 177).…”
Section: Introductionmentioning
confidence: 99%
“…However, the various layers of subcontractors involved in typical transport processes make it difficult to verify environmentally friendly standards [26,27]. By having such information on the blockchain, customers would be able to trace the goods back to the first node in the chain of transport, providing insight to the chosen transport route and the carrier choice.…”
Section: Relative Advantagementioning
confidence: 99%
“…Wang et al [63] found that green logistics performance would impose positive effects to the exporting countries in the international trade. Herold and Lee [64] investigated the carbon reports disclosed by some giant international logistics enterprises, e.g., UPS, FedX and DHL, and compared their sustainability-…”
Section: Evaluation On the Social Environmental And Economic Impactsmentioning
confidence: 99%